KORELASI KADAR PLUMBUM DALAM DARAH DENGAN GANGGUAN KOGNITIF PADA PETUGAS STASIUN PENGISIAN BAHAN BAKAR UMUM KOTAMADYA YOGYAKARTA - , Noegroho Harbani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Lead exposure is neurotoxic, especially to hypocampus. Lead is affecting retention of short-term memory in cell cytoplasm and storage of long-term memory in nucleus. Lead in low concentration impairs Ca homeostasis intracellular and neurotransmitter release both centrally and peripherally, such as dopamine, acetylcholine, and GABA. Acetylcholine peripherally influences muscle and related to memory process and cognitive in central nervous system. The aim of this study is to discover the correlation between blood lead level Pb and cognitive decline. This is a cross-sectional study. We examined blood lead level of SPBU workers randomly and we used Mini-Mental State Examination (MMSE) to measure cognitive decline. Correlation of blood lead level with cognitive decline was statistically analyzed. There were 55 total subjects, 9 (16.3%) subjects had high Pb level (>20 Î¼g/dL) with mean blood Pb level 5.3 (0.07-34.24) Î¼g/dL. 37 (67.3%) subjects had cognitive decline, divided into orientation 22 (40%) subjects, registration 0, attention 31 (56.4%) subjects, recall 27 (49.1%), language 1 (1.8%) and visuospatial 0. From Spearmann correlation analyzes, we found a weak negative correlation of blood Pb level with cognitive decline (r= -0.301